Divergent strains of human immunodeficiency virus type 1 circulating in India, subtyped by heteroduplex mobility assay - Sahni A; Kapila K; Gupta R (Wolters Kluwer Medknow Publications, 2008)
Genomic variations in HIV-1 represent a major problem in understanding disease progression, studying drug resistance and developing effective vaccines. Heteroduplex Mobility Assay (HMA) was used for analyzing HIV-1 subtypes resulting from genetic similarity or divergence of C2 -V3 -V5 region of envelope gene between HIV-1 strains obtained from clinical samples in a tertiary care center at Pune. DNA from the PBMCs of infected individuals was amplified by nested PCR. Heteroduplexes were then formed by denaturing DNA from the unknowns with DNA from the reference strains. The results were analyzed by polyacrylamide gel electrophoresis. Out of 177 samples analyzed, 170 were of subtype C (96%). Four samples were found to be of subtype B (2.2%); in three samples, no definitive assignment of subtype was possible by HMA and these perhaps could be circulating recombinant forms (CRFs) of HIV-1. These findings may have significant implications toward development of a candidate vaccine for India.